The Effects of Competency, Training, and Career Development on Employee Performance at i3L - Wiwiek Setiawati; Witya Maulida; Iu Rusliana; Fairuz Arta Abhipraya (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This study examines the effect of competency, training, and career development on employee performance at the i3L staff. By utilizing 80 respondents from the i3L staff level obtained from the saturated sampling technique, the researcher used a quantitative research framework with survey data collection techniques using an ordinal Likert scale of 1-5. The researcher used SEM-PLS analysis using the SmartPLS 4 application as a data processing tool. This study concludes that the original sample (O) value is 0.400 for the competency variable, indicating a positive effect on performance, with 2.515 > 1.96 as the T Statistics value and a P value of 0.012 <0.05 indicating the competency variable has a significant effect on performance. The career development variable found an original sample value (O) of 0.538, which indicates a positive effect on performance, with a T statistic value of 3.262 > 1.96 and a P value of 0.001 <0.05, which indicates a significant effect on performance. So, if the effect of competency and career development variables on performance is positive and significant, these two variables, H0, are rejected, but H1 is accepted. In the training variable on performance, the original sample value (O) was found to be 0.051, which indicates a positive effect on performance. However, it was also found that the T statistical value of the training variable on performance was 0.369 < 1.96, with P values having a value of 0.712 > 0.05, which indicated that the effect was not significant. Because of this, i3L needs to improve more on suitable training programs to improve the performance of employees.